Development of new optimal cloud computing mechanism for data exchange based on link selectivity, link reliability and data exchange efficiency - Reddy, K. Shirisha; Balaraju, M.; ., Ramananaik (International Journal of Engineering and Technology, 2017)
Reorganization of virtual machines (VM) presents an extraordinary opportunity for parallel, cluster, grid, cloud and distributed computing. Virtualization technology benefits the computing and IT ventures by enabling clients to share expensive by multiplexing virtual machines on a similar arrangement of hardware hosts. With the advantage of higher data-accessing feature, this data sharing approach provides challenges in perceptive to data security and data integrity issues. In this paper, to the selected network, a service level agreement approach for data access resource management is developed. During the exchange of packets over the selected link, it is required that data are to be accessed at a faster rate. The overhead may have serious negative effects on cluster utilization, throughput, and Quality of Service issues. Therefore, the challenge is to develop VMs a control approach, which governs the rate allocation in terms of data access and bandwidth to speed the data exchange performance. The throughput of the network is monitored by the traffic link rate, wherein the processing overhead is observed at the process of quality.